(untitled) (Al-Academy, 2019)
The research (Virtual Reality Technology and its Uses in Industrial Product Design) is interested in the virtual reality technology used in the industrial product design and consequently knowing the functions achieved in the industrial product according to the data of that technology which participates in activating the mental and imaginary image of the user which show the parameters of the technical transformation of that product. The terms used in the research have been defined to guide the reader. The second chapter, the theoretical framework consisted of three sections the first is concerned with technology in the industrial design. The second is concerned with the virtual environment and the virtual reality. The thirds chapter consists of the research methodology wherein the research community was chosen, which included two global electronic industries companies. The research sample was deliberately chosen according to the research objectives, which contained three models. The models were analyzed according to the content analysis method. The method used three samples from the research community which is the research community available in the global electronic industries companies during the research period, according to the sample analysis method, and according to the analysis axes derived from the theoretical framework indicators. It also consisted of sample description and analysis according to the form of determining the axes of the analysis. The fourth chapter contains the results, conclusions reached at by the researcher, recommendations and suggestions as well as the appendices and a table of the research community